2016
DOI: 10.1007/s10843-016-0171-2
|View full text |Cite
|
Sign up to set email alerts
|

The online–offline balance: internationalization for Swedish online service providers

Abstract: Online service providers (OSPs) are becoming increasingly important in the global economy and are undertaking internationalization at a remarkable speed. Since they depend on digital delivery over the internet, OSPs are portrayed as footloose in their geographical expansion and are often described as Bborn global.^However, on the basis of three case studies, the paper reveals the importance of the home market as a springboard, and of regional expansion in the early phase of internationalization. The paper emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 84 publications
2
74
0
Order By: Relevance
“…Third, we found that REs’ internationalization approach had the character of born globals (i.e., with early internationalization attempts), but at the same time only had regional reach. From an internationalization theory perspective, our findings are aligned with Kim (2003) and Wentrup (2016) in that most digital start-ups internationalize regionally in the early stages of the internationalization process. The emerging market factor does not seem to change this pattern.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Third, we found that REs’ internationalization approach had the character of born globals (i.e., with early internationalization attempts), but at the same time only had regional reach. From an internationalization theory perspective, our findings are aligned with Kim (2003) and Wentrup (2016) in that most digital start-ups internationalize regionally in the early stages of the internationalization process. The emerging market factor does not seem to change this pattern.…”
Section: Discussionsupporting
confidence: 69%
“…Today, the literature about born globals is abundant, (Andersson, 2011; Gabrielsson & Gabrielsson, 2011; Madsen & Servais, 1997; Moen, 2002) although there is still no consensus on a clear definition of the term. Internationalization is embedded in the digital economy (Kim, 2003; Wentrup, 2016). The internet enables firms to grow fast in general as well as quickly over a wide geographic range due to low market entry barriers and network effects (Rochet & Tirole, 2003, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These factors may include economic differences, language differences, and cultural orientation, different political, and institutional systems that make more difficult for a firm to fully understand crucial aspect of foreign market business environments and fully enter the market (Ruzzier, Robert, & Hisrich, ). Thus, economic and technological barriers can constrain small business from internationalising (Lee & Chung, ; Wentrup, ). However, this study will consider the economic barriers of SMEs internationalisation as postulated by Uppsala theoretical model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research also recognizes the importance of users. As we summarize in Web Appendix A, the emerging literature on digital internationalization not only explores supply-side factors such as firm resources (e.g., Cahen and Borini 2020; Mahnke and Venzin 2003) and strategies (e.g., Watson et al 2018; Wentrup 2016) but also highlights the role of users in facilitating digital internationalization (e.g., Chandra and Coviello 2010; Shaheer and Li 2020). What this research stream ignores, however, is the location-boundedness of user interactions; digital firms interacting with users in certain lead markets can be more likely to improve the global appeal of their technologies compared with firms first penetrating their technologies elsewhere.…”
mentioning
confidence: 99%